Ascaris suum Cuticle Ultrastructure Due to the In Vitro Application of Ethanol Extract to Fruits Musa x paradisiaca L. ‘Pisang Ambon’ - Dwi Haryatmi; Okid Parama Astirin; Tetri Widiyani (Biosaintifika: Journal of Biology & Biology Education, 2018)
Species of Musa have various activities, one of which is anthelmintic activity. Part of banana plants that can be used as anthelmintic is part of the fruit, because of the phytochemical content possessed. Tannin is able to inhibit the enzyme cholinesterase, damage the membrane of the worm and can precipitate the protein.  The purpose of this research is to know the content of tannin and also total tannin level on ethanol extract of Musa x paradisiaca L. ‘Pisang Ambon’ and in vitro effect of the extract on Ascaris suum cuticle.  Thin Layer Chromatography (TLC) showed of ethanol extract of Ambon banana containing tannin with a total test of tannin was 54.98% w/w. In vitro at negative control (NaCl 0.9%) worm death occurred at 289 hours, positive control (pyrantel pamoate 5 mg/ml) at 1 hour, extract concentration 200 mg/ml at hour 27 and concentration 400 mg/ml at 1 hour. Histopathological examination and scanning electron microscope showed a degenerative change in ultrastructures of the worm's cuticle. From the results of this study, it can be concluded that exposure of ethanol extract to Ambon banana give a damaging effect to cuticle ultrastructure in the form of crack/break, perforation and separation of muscular from cuticle and edema on A. suum worm. High tannin content in the raw/green ambon banana, can be developed to eradicate ascariasis including egg stage which until now cannot be done with synthetic drugs due to the thickness and strength of layers of worm eggs consisting of layers of protein and lipids.